Efektivitas Metode One Day One Ayat (ODOA) Dalam Menghafal Al-Qur’an Di Pondok Pesantren Syarif Ar-Rasyid Deli Serdang - Ridwan Ghojali; Hotni Sari Harahap; Ade Rahman Matondang (Journal of Innovative and Creativity, 2025)
This study aims to examine the effectiveness of the One Day One Ayat (ODOA) method in improving Qur’anic memorization among students at Pondok Pesantren Syarif Ar-Rasyid. Using a quantitative descriptive approach, data were collected through questionnaires, observations, and interviews with 30 students who had participated in the ODOA program for at least one month. The results showed that the ODOA method was effective in enhancing the quantity and consistency of memorization. Students were able to meet daily targets and showed increased motivation, discipline, and spiritual connection during the memorization process. The findings also indicate that the structured nature of the ODOA method helped develop a sustainable memorization habit without overwhelming students. The environment of the pesantren, support from teachers, and daily routines played a significant role in the success of this method. Therefore, the ODOA method is considered a practical and impactful strategy in improving Qur’an memorization, especially when supported by proper guidance and consistency.